How Heat Waves Influence Project Performance in the Construction Industry? - Azmi, Anis Shafiqah; Yaman, Siti Khaljiah; Mohammad, Hairuddin (Journal of Structural Monitoring and Built Environment, 2025)
Heat waves in Southeast Asia are becoming increasingly common and intense, posing substantial challenges for the construction industry. As the heat waves are predicted to increase in the future, they will certainly impact construction project performance, specifically in terms of cost, time, and quality. This paper aimed to analyze the impact of heat waves on these project performances. A questionnaire survey using Microsoft Forms was used to gather the data. This paper focuses on 200 respondents from Grade 6 (G6) and Grade 7 (G7) contractors in Johor Bahru, Johor. The findings show the interrelated effects on time, cost, and quality. The productivity of workers decreased as they required a longer time to rest, which led to delay issues. Additionally, exposure of the material to heat and workers’ focus on work influence the poor quality of the project. The heat forcing in additional safety measures and heat-related illnesses necessitate more labor, further escalating project costs. Therefore, the paper concludes that heat waves influence construction in Malaysia through an increased duration cost and risk of project completion associated with quality.